An exploratory study of the suitability of help-seeking, culture and stigma measurement among university students - Kesantini Athinarayanan Rao; Getrude C.Ah Gang (Southeast Asia Psychology Journal, 2023)
There is a rise in the incidence and prevalence of mental distress among university students. However, the rate of mental health service utilisation is low. As psychological help-seeking attitude is a strong predictor for seeking psychological treatment, it is important to validate feasible and psychometrically sound instruments in the Malaysian context. This pilot study aimed to investigate the reliability and validity of six scales measuring the moderating role of culture on the effect of stigma in psychological help-seeking attitudes among university students. An online questionnaire, consisting of 83 items and 6 scales namely, the Portrait Value Questionnaire (PVQ-21), Loss of Face Scale (LOF), Individualism versus Collectivism Scale (INDCOL), Perceptions of Stigmatisation by Others for Seeking Psychological Help Scale (PSOSH), SelfStigma of Seeking Help (SSOSH), and The Attitudes Toward Seeking Professional Psychological Scale (ATSPPHS-SF) is distributed to a convenience sample of 61 samples from International Islamic University Malaysia. The results of this pilot study indicated that the overall reliability of the questionnaire was Cronbach’s Alpha 0.90. The Cronbach Alpha value for the total of all measures was found to be highly reliable. A factor analysis was run to test the validity of the unidimensional scales, and the results ranged from KMO value 0.63 to 0.84 with Bartlett’s p-value for all scales being significant (p <0.00). Validity of multidimensional scales were tested with convergent validity analysis. Both the INDCOL and PVQ-21 showed a good convergent validity and is a valid tool. The instruments used in this pilot study can be used for the main research study in studying the moderating role of culture on the effect of stigma in psychological help-seeking attitudes among university students as the instruments are multiculturally competent. Therefore, in a multicultural population like Malaysia, instruments as such are found to be helpful in studying the effects of culture, stigma, and personal values on psychological help-seeking attitudes.